Evolution of the goat feeding advisory plan in Murcia: Structure and follow-up - Haba E.; Ciria J.; Riquelme M.M.; Díaz C.; Carrizosa J.A.; Falagán A. (Production systems and product quality in sheep and goats, 2001)
The goat feeding advisory plan of Murcia (PAAC), has permitted the establishment of feeding patterns for the Murciano-Granadina goat breed, on the basis of the production systems and the products used as feeding complement to shepherding. The proposed feeding strategy is based on the periodic calculation of rations to complement grazing while shepherding in private goat breeding farms in the Murcia Region, and its later follow-up. The work carried out in different private farms has revealed numerous particularities of a practical nature in the handling of the Murcia milk-goat feeding.
Meeting of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1999/09/23-25, Molina de Segura-Murcia (Spain)